2004
DOI: 10.1103/physrevlett.93.248101
|View full text |Cite
|
Sign up to set email alerts
|

Limited Slowdown of Endocrine-Disruptor Diffusion in Confined Fluid Lipid Membranes

Abstract: Self-diffusion rates of lipids and trapped bisphenol A (BPA) are determined in various sizes of confined but fluid membranes by high-field-gradient NMR at 600 MHz. Micelles and vesicles of 3- to 400-nm diameters are used as model membranes to get an insight into the molecular diffusion in such soft environments. The slowdown of BPA and lipid motions is leveled off in 100- and 400-nm vesicles, although the hydrodynamic continuum model gives the aggregate motion slowed inversely to the aggregate size. Instead, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 19 publications
3
25
0
1
Order By: Relevance
“…1, conditioned by the experimental time scale. If the time scale is not long enough, the D value of the drug is not necessarily equal to the value of the membrane molecule 25 , while it is a certain measure of the molecular mobility in the lipid vesicular membrane 26 . The measurements were repeated 2-4 times at 30 where the lipid was in the fluid liquid-crystalline L α phase.…”
Section: Vesicle Preparationmentioning
confidence: 99%
“…1, conditioned by the experimental time scale. If the time scale is not long enough, the D value of the drug is not necessarily equal to the value of the membrane molecule 25 , while it is a certain measure of the molecular mobility in the lipid vesicular membrane 26 . The measurements were repeated 2-4 times at 30 where the lipid was in the fluid liquid-crystalline L α phase.…”
Section: Vesicle Preparationmentioning
confidence: 99%
“…/s for FBPA [8,13,17], the mobility significantly slowed down as compared to that of the free component. Interestingly, D B of both drugs is almost comparable to that of the lipid molecules 0.1 10 10 m 2 /s in LUV [8,13], indicating that the molecular motion in the soft membrane environment is closely related to the intramembrane fluidity [8,9].…”
mentioning
confidence: 72%
“…It is an extension of the high-field-gradient NMR study on the mobility of lipids and trapped drugs in fluid lipid membranes [9]. Okamura and Yoshii have succeeded in distinguishing both bound and free states of the drug in situ, to quantify how much of the drug is bound to the membrane without any separation procedures of the bound and the free species.…”
mentioning
confidence: 99%
“…Thus, the conversion between P and M enantiomers of 5HM is suppressed, resulting in the fixation of the M enantiomer. This explanation may be supported by a 1 H-NMR study 15 which demonstrated that a guest molecule in small-sized vesicles rotates more rapidly than that in large-sized vesicles.…”
Section: Chiral Discrimination Of Pc Vesicles With Various Sizesmentioning
confidence: 87%